Strategi Guru Dalam Mendidik Anak Berkebutuhan Khusus Di TK Lembayung Indah Kota Bengkulu - Santi, Santi; Margaretha, Lydia; Rulismi, Dwi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study is to determine the strategies used by teachers in educating children with special needs at Lembayung Indah Kindergarten in Bengkulu City. The type of research used in this study is descriptive qualitative research. The data collection methods used are interviews, observation, and documentation. Based on the data analysis conducted using observation, interviews, and documentation, the data sources were the classroom teachers and the principal of TK Lembayung Indah in Bengkulu City, and the documentation consisted of photos taken during interviews with the classroom teachers and the principal. The results of this study can be summarised as follows: describing the strategies used by teachers in educating children with special needs at TK Lembayung Indah in Bengkulu City, speech delay and dyslexia are: 1) teachers' strategies in understanding the characteristics of children with speech delay and dyslexia, 2) teachers' strategies in using teaching media to educate children with speech delay and dyslexia, 3) teachers' strategies in using media and methods to educate children with speech delay and dyslexia, 4) teachers' strategies in implementing innovative learning, 5) teachers' strategies in communicating with children with special needs, 6) Ability to create a safe and comfortable environment both inside and outside the classroom. This can be summarised as: understanding the needs of children, creating a supportive learning environment, frequently engaging children in slow, clear, and proper language, and utilising technological aids such as laptops and mobile phones. Meanwhile, strategies for children with dyslexia include: a) using multisensory learning methods, b) using structured teaching, and c) focusing on the development of reading skills.